ISBAT NIKAH AND CHILD STATUS IN PERSPECTIVE OF ISLAMIC MARRIAGE LAW (STUDY AT RELIGION COURTS IB DONGGALA) - Wahyuni, Erni (Tadulako Master Law Journal, 2018)
The research goals are to study and describe the consideration of the jugde inrelated to status of the marriage child, before isbat nikah, as well as to describe the implication to the child born before isbat nikah. The research method used is juridical normative jurisdiction, the data used are secondary data. The data analysis was done by qualitative analysis. The results of research in this thesis turned out to be, not all requests of marriage confirmation of undocumented marriages can be granted. Religious Court will grant the confirmation of marriage that qualified one of criteria in Article 7, paragraph (3) letter a to letter e Compilation of Islamic Law and the marriage proven at trialappropriate according to Islamic Law, and theres no violation ofmarriage banaccording to Islamic law and state law.